{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# 2_3 - Chapter 2 Graphs 2.3 1 Circles 2(x 2 2 = 4 x 2 = 2...

This preview shows pages 1–5. Sign up to view the full content.

Chapter 2 226 Graphs 2.3 Circles 1. add, 4 2. ( x - 2) 2 = 4 x - 2 = ± 2 x - 2 = 2 x = 4 x - 2 = - 2 x = 0 The solution set is 0,4 { } . 3. True 4. radius 5. True 6. (2,–5), 6 7. Center = (2, 1) Radius = distance from (0,1) to (2,1) = (2 - 0) 2 + (1 - 1) 2 = 4 = 2 ( x - 2 ) 2 + ( y - 1) 2 = 4 8. Center = (1, 2) Radius = distance from (1,0) to (1,2) = (1 - 1) 2 + (2 - 0) 2 = 4 = 2 ( x - 1) 2 + ( y - 2) 2 = 4 9. Center = midpoint of (1,2) and (4,2) = 1 + 4 2 , 2 + 2 2  = 5 2 ,2 Radius = distance from 5 2 ,2 to (4,2) = 4 - 5 2 2 + (2 - 2) 2 = 9 4 = 3 2 x - 5 2 2 + ( y - 2) 2 = 9 4 10. Center = midpoint of (0,1) and (2,3) = 0 + 2 2 , 1 + 3 2  = 1,2 ( 29 Radius = distance from 1,2 ( 29 to (2,3) = 2 - 1 ( 29 2 + (3 - 2) 2 = 2 x - 1 ( 29 2 + ( y - 2) 2 = 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Section 2.3 Circles 227 11. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 0 ) 2 + ( y - 0) 2 = 2 2 x 2 + y 2 = 4 General form: x 2 + y 2 - 4 = 0 12. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 0) 2 + ( y - 0) 2 = 3 2 x 2 + y 2 = 9 General form: x 2 + y 2 - 9 = 0 13. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 1) 2 + ( y - - 1 ( 29 ) 2 = 1 2 x - 1 ( 29 2 + ( y + 1) 2 = 1 General form: x 2 - 2 x + 1 + y 2 + 2 y + 1 = 1 x 2 + y 2 - 2 x + 2 y + 1 = 0 14. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - - 2 ( 29 ) 2 + ( y - 1) 2 = 2 2 ( x + 2) 2 + y - 1 ( 29 2 = 4 General form: x 2 + 4 x + 4 + y 2 - 2 y + 1 = 4 x 2 + y 2 + 4 x - 2 y + 1 = 0
Chapter 2 Graphs 228 15. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 0 ) 2 + ( y - 2) 2 = 2 2 x 2 + ( y - 2) 2 = 4 General form: x 2 + y 2 - 4 y + 4 = 4 x 2 + y 2 - 4 y = 0 16. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 1) 2 + ( y - 0) 2 = 3 2 ( x - 1) 2 + y 2 = 9 General form: x 2 - 2 x + 1 + y 2 = 9 x 2 + y 2 - 2 x - 8 = 0 17. ( x - h ) 2 + ( y - k ) 2 = r 2 ( x - 4 ) 2 + ( y - ( - 3)) 2 = 5 2 ( x - 4 ) 2 + ( y + 3) 2 = 25 General form: x 2 - 8 x + 16 + y 2 + 6 y + 9 = 25 x 2 + y 2 - 8 x + 6 y = 0 18. ( x - h ) 2 + ( y - k ) 2 = r 2 x - 2 ( 29 2 + y - - 3 ( 29 ( 29 2 = 4 2 x - 2 ( 29 2 + y + 3 ( 29 2 = 16 General form: x 2 - 4 x + 4 + y 2 + 6 y + 9 = 16 x 2 + y 2 - 4 x + 6 y - 3 = 0 19. ( x - h ) 2 + ( y - k ) 2 = r 2 x - - 3 ( 29 ( 29 2 + y - - 6 ( 29 ( 29 2 = 6 2 x + 3 ( 29 2 + y + 6 ( 29 2 = 36 General form: x 2 + 6 x + 9 + y 2 + 12 y + 36 = 36 x 2 + y 2 + 6 x + 12 y + 9 = 0

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Section 2.3 Circles 229 20. ( x - h ) 2 + ( y - k ) 2 = r 2 x - - 5 ( 29 ( 29 2 + y - 2 ( 29 2 = 5 2 x + 5 ( 29 2 + y - 2 ( 29 2 = 25 General form: x 2 + 10 x + 25 + y 2 - 4 y +
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}